Estimasi Karbon Tersimpan pada Alang-Alang (Imperata cylindrica Beauv.) di Lahan Kering - Agustina Hariana; Aditya Rahman; Gunawan Gunawan (Bioscientiae, 2020)
As an effort to reduce greenhouse gas emissions, then amount of CO2 in the air must be controlled by increasing the amount of CO2 absorption by plants as much as possible and supress CO2 emissions into the air as low as possible.Â  This research was conducted in order to obtain information about the amount of carbon stored in Imperata cylindrica which grows in dry land areas. Sampling method is done by purposive in consideration with the distribution of this plant group.Â  Measurement of carbon stored includes the measurement of biomass, organic carbon measurement on I. cylindrica and measurements of carbon stored. The data obtained are analysed statistically and analysed with the parametric one way ANOVA. The results obtained that the carbon stored in I. cylindrica on dry land of Cempaka District consecutive 67.55 g.m-2, 116.25 g.m-2, and 96.63 g.m-2